The Fragmentation of Political Science and “Methodological Pluralism”: Regionalism and Geopolitics - Vilanova, Pere (Geopolítica(s). Revista de estudios sobre espacio y poder, 2014)
The relationship between our academic tools (Political Science broadly speaking) and the object of our study and research (the world as a global political system) is totally dysfunctional. The world, as an empirical political object, has changed more in the past sixty years (with particular emphasis in the last twenty years) than our academic disciplines and structures. This malfunction is becoming critical and the prospects are quite dark, not only in terms of our prognosis or prospective capacity, but simply our capacity to describe ―therefore to analyze― reality with a minimum of consistency. If you add this structural problem to the debate over the legitimacy of “methodological pluralism” and also the academic micro fragmentation of our programs (both nationally and at a transnational level), we are in trouble. We need to assess the situation and see if we can re-direct our tools. And in any case, we will continue to work on a trial-and-error basis. In order to proceed, this paper will trace the evidence of the importance of these issues over the main international academic activities of our communities (Political Science, Sociology, International Relations, etc.), as expressed in International Congresses or Sessions of institutions as IPSA (International Political Science Association), ISA (International Sociological Association), or ECPR (European Consortium for Political Research). This is the reason why this paper refers to what is generally identified as the “Main Theme” of a specific World Congress, within which we can trace the importance given to the topic by different Panels, Working Groups or Research Committees. Of course, another strategy which could be followed by others interested in the problem raised by this paper should be via an empirical analysis of academic publications, papers, readings and Academic Programs (but this second approach is far too ambitious to be handled in a single Paper like the current one).